Penerapan Sistem Pendukung Keputusan Berbasis Web Untuk Perencanaan Aktivitas Edukasi Dan Hiburan Di Panti Asuhan Menggunakan Metode Fuzzy AHP - Moh Rere Velentino Zantohar; Dandi Sunardi; Harry Witriyono; Muntahanah Muntahanah (Jurnal Media Infotama, 2024)
Educational and entertainment activities in orphanages are important aspects in helping the physical, mental and social development of children living in these institutions. Orphanages often serve as homes for children who do not have access to a family or a stable educational environment. Therefore, organizing educational and entertainment activities in orphanages is a must to provide positive experiences to these children, helping them grow and develop well. for each individual. The proposed solution is to use a web-based decision support system. This system will help orphanage managers plan educational and entertainment activities more efficiently. The main advantage of using the Fuzzy Analytical Hierarchy Process (AHP) method in this system is its ability to overcome uncertainty and ambiguity that often arises in planning in orphanages. Fuzzy AHP allows assessment and decision making based on uncertain or fuzzy data. This will be especially useful in assessing children's preferences and needs that may be difficult to measure with precision.